2019
DOI: 10.1021/acs.langmuir.9b02357
|View full text |Cite
|
Sign up to set email alerts
|

Direct Nanoscopic Measurement of Laminar Slip Flow Penetration of Deformable Polymer Brush Surfaces: Synergistic Effect of Grafting Density and Solvent Quality

Abstract: A detailed quantitative nanoscopic description of soft surfaces under dynamic flow is lacking, despite its importance. To better understand the role of surface texture in nanoscopic mass transport in complex media, we used Forster resonance energy transfer in combination with total internal reflectance fluorescence microscopy (FRET-TIRFM) to directly measure laminar slip flow penetration depth (slip length) on poly(N-isopropylacrylamide) (pNIPAM) thin films (50−110 nm) of different grafting densities (0.60, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Similar to post-polymerization modification, pre-polymerization modification involves the anchoring of functional moieties to the surface; however, in this case the functional moieties are tethered to a linker and the polymers are subsequently grown/tethered to the functional moiety itself. [73][74][75] This technique allows for the position of the functional moieties to be precisely known at all degrees of solvation.…”
Section: Pre-and Post-polymerization Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to post-polymerization modification, pre-polymerization modification involves the anchoring of functional moieties to the surface; however, in this case the functional moieties are tethered to a linker and the polymers are subsequently grown/tethered to the functional moiety itself. [73][74][75] This technique allows for the position of the functional moieties to be precisely known at all degrees of solvation.…”
Section: Pre-and Post-polymerization Modificationmentioning
confidence: 99%
“…As the acceptor solution penetrates the polymer brushes, FRET can be observed between the anchored donor and solvated acceptor and the degree to which the donor fluorescence is quenched can be used to determine slip length. This technique allowed them to investigate not only penetration depth (slip length) of the acceptor through the polymer brushes [73] but also the effect of polymer brush grafting density [75] and solvent quality [74,75] on the penetration depth.…”
Section: Pre-and Post-polymerization Modificationmentioning
confidence: 99%
“…Usually, the interfacial slip can be greatly restrained by constructing the hydrogen-bonded network structure at the liquid−solid interfaces, which can explain why the dynamic shear flow has a weaker effect on the interfacially anchored hydrophilic polymer layers. 37,38,43,47,85 To strengthen the interfacial hydrogen bonding interaction, available approaches have been reported. A number of studies have indicated that the charged interaction can induce the formation of strong hydrogen-bonded network structures.…”
Section: Controlling the Slip Flowmentioning
confidence: 99%
“…In general, the techniques can be divided into two main categories. One is to trace the flow near a boundary by tracer particles using confocal, total internal reflectance fluorescence microscopy (TIRFM) or stimulated emission depletion (STED). The other is based on the force or displacement response, such as atomic force microscopy (AFM), surface forces apparatus (SFA), X-ray, and neutron reflectometry (NR). Although the mutual interaction between tracer particle probes and solid surfaces might be an issue to be evaluated, such experimental results were of great value and worth discussing, from which the microscopic mechanism of the interfacial slip could be revealed.…”
Section: Direct and Indirect Observation For Slip Flowmentioning
confidence: 99%
See 1 more Smart Citation